Development of Tamil children literature during the sanggam period - Sivakumar, S. (2014)
This study is an analysis that involves the Development in the History of Tamil Children's Literature during the Sanggam Period. It is rather difficult to ensure the existence of children literature. Besides, literature has long existed and still exists for many years. Development in children literature has always been connected with two persons or two main characters that are the children themselves and their ancestors. In addition, the presence of children literature in nineteenth century is considered as the inner power for the development of current Tamil Literature. The very first grammar book 'Tholknppiynm' and other scriptures in 'Sanggam Period' also gave information about children literature.